2016
DOI: 10.1007/s12035-016-9686-8
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 Regulates the Proliferation of Cochlear Supporting Cells Via the Canonical Wnt Signaling Pathway

Abstract: Cochlear supporting cells (SCs), which include the cochlear progenitor cells, have been shown to be a promising resource for hair cell (HC) regeneration, but the mechanisms underlying the initiation and regulation of postnatal cochlear SC proliferation are not yet fully understood. Bmi1 is a member of the Polycomb protein family and has been reported to regulate the proliferation of stem cells and progenitor cells in multiple organs. In this study, we investigated the role of Bmi1 in regulating SC and progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 34 publications
1
68
0
Order By: Relevance
“…Sphere-forming assays have been used to evaluate cell proliferation in many studies (Li et al, 2003; Sinkkonen et al, 2011; Chai et al, 2012; Shi et al, 2012; Jan et al, 2013; Lu et al, 2016). To determine the sphere-forming ability of Lgr5+ progenitors and Lgr5- SCs, we purified the two cell populations by flow cytometry, cultured 200 sorted cells at a density of 2 cells/μl in a Costar ultra-low attachment plate for 5 days, and counted the number of spheres before passage to the next generation ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphere-forming assays have been used to evaluate cell proliferation in many studies (Li et al, 2003; Sinkkonen et al, 2011; Chai et al, 2012; Shi et al, 2012; Jan et al, 2013; Lu et al, 2016). To determine the sphere-forming ability of Lgr5+ progenitors and Lgr5- SCs, we purified the two cell populations by flow cytometry, cultured 200 sorted cells at a density of 2 cells/μl in a Costar ultra-low attachment plate for 5 days, and counted the number of spheres before passage to the next generation ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Lgr5 is widely expressed in the cochlear duct prosensory region during embryonic development, but it becomes restricted to a subset of SCs after birth (Chai et al, 2011). Recently, Lgr5+ cells in newborn mice have been shown to be a population of HC progenitors that can regenerate HCs through both direct differentiation and through mitotic regeneration (Chai et al, 2012; Shi et al, 2013; Bramhall et al, 2014; Cox et al, 2014; Hegarty et al, 2015; Wang et al, 2015; Lu et al, 2016). However, the detailed gene expression profile differences between the Lgr5+ progenitors and the Lgr5- SCs have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cochlear Lgr5+ progenitors can generate HCs in the neonatal mouse in vivo [6, 25, 26]. First we identified the Lgr5-EGFP expression in the apical and the basal turn of the postnatal day (P)2 mouse cochlea.…”
Section: Resultsmentioning
confidence: 99%
“…Sphere-forming ability has been used in multiple studies as one criterion to evaluate the cells' capacity as progenitors in the inner ear [6, 13, 23, 25, 26, 28]. Recent studies showed that Lgr5+ progenitors have higher sphere-forming ability and can generate more Myo7a+ HCs than other SCs [6, 25].…”
Section: Resultsmentioning
confidence: 99%
“…In the neonatal cochleae of mammals, the Wnt target gene Lgr5 is expressed in a subset of SCs (the pillar cells, inner phalangeal cells, and Deiters' cells) [54], and these endogenous Lgr5+ cells maintain mitotic quiescence. The expression level of Wnt signaling pathway including Lgr5 regulated via the expression of Bmi1 [55]. When isolated as single cells using flow cytometry and cultured in vitro, they become proliferative and converted into HC-like cells [13].…”
Section: Hair Cell Regenerationmentioning
confidence: 99%